Effects of Bariatric Surgery on Cardiac Structure and Function: A Systematic Review and Meta-Analysis - Cuspidi, Cesare; Rescaldani, Marta; Tadic, Marijana; Sala, Carla; Grassi, Guido (American journal of hypertension, 2014)
BACKGROUND Morbid obesity, a condition increasingly treated with bariatric procedures, is strongly associated with left ventricular (LV) hypertrophy and impaired LV function. We analyzed the literature to provide comprehensive information on cardiac structural and functional changes, as assessed by imaging techniques, after bariatric surgery. METHODS The studies were identified by the following search terms: "bariatric surgery," "obesity," "left ventricle," "left ventricular hypertrophy," "cardiac hypertrophy," "ventricular dysfunction," "left ventricular hypertrophy regression," "echocardiography," "magnetic resonance imaging," and "cardiac imaging techniques." RESULTS In a pooled population of 1,022 obese subjects with preserved systolic function included in 23 studies, bariatric procedures induced (i) a decrease in LV mass (standardized mean difference (SMD) = −0.46; P < 0.001) and relative wall thickness (SMD = −0.20; P < 0.001); (ii) an improvement of LV diastolic function, as reflected by the increase in mitral flow E/A ratio (SMD = +0.39; P < 0.001); (iii) a decrease in left atrium diameter (SMD = −0.26; P < 0.001); or (iv) no changes in LV ejection fraction (SMD = +0.03; P = 0.46). CONCLUSIONS The present meta-analysis, the largest to date focusing on cardiac structural and functional changes in morbidly obese subjects after bariatric surgery, documents that this therapeutic approach exerts important cardioprotective effects in terms of regression of LV hypertrophy, improvement of LV geometry and diastolic function, and reduction of left atrial size.